دور حاضنات الأعمال في دعم المشاريع المقاولاتية المحلية - محضنة المؤسسات الصغيرة والمتوسطة لولاية بسكرة نموذجا - قرود, علي; كزيز, نسرين (Université de M'sila, 2018)
This study highlights the role of business incubators in supporting local resisprojects through the study of the situation of small enterprises and medium for a state with sugar by addressing how the institutions ' nursery has contributed to the state Biskrain support and accompaniment of local resisprojects, as a goal to look at the content of activating the role that business incubators can play in supporting and sustaining small and medium enterprises and developing its work to advance the prestige of successful institutions that represent a starting point and economic takeoff in accordance with the contents of sustainable development, and to this end Adoption of the field study of the subject of study, the study concluded that the incubators in the study were actively involved in the incubation and accompaniment of local incubating institutions.
Keywords: small and medium enterprises, business incubators, economic development, and a Biskra nursery.